Aroma Profiling and Shelf-Life Extension Method of Australian Black Périgord truffle (Tuber melanosporum) - Choo, Kenny Sing Ong (Curtin University, 2024)
This study aimed to identify the aroma profile and bacterial community structure of Australian grown black Périgord truffle (Tuber melanosporum). This study also determines the efficiency of edible coatings, antimicrobial agents, antioxidants and edible coatings incorporated with antimicrobial agents in truffle shelf-life extension. Furthermore, the efficiency of truffle aroma preservation by encapsulating truffle aroma volatiles in a food matrix without retaining the truffle’s fruit body was accessed.